Penerimaan Keluarga dan Kesehatan Mental pada Gay dengan HIV Positif - Alex R I Ompusunggu; Eztefania Dorantez (Yayasan Literasi Sains Indonesia, 2026)
This study is a literature review that examines the relationship between family acceptance and mental health among gay individuals with HIV positive status, emphasizing psychosocial dynamics in various cultural contexts, including Indonesia. By synthesizing indexed journal articles published in the period 2015–2025 using keywords such as “family acceptance,” “HIV gay mental health,” and “stigma,” this review finds a consistently positive relationship between family acceptance and mental health (combined r = 0.42, p < 0.001 in several meta-analytic subsets). High family acceptance has been shown to reduce symptoms of depression and anxiety by around 25–35%, as well as suppress the impact of HIV-related stigma, particularly in collectivist societies where family rejection exacerbates psychological distress. Key emerging themes include the role of emotional support as a resilience factor in young adults (18–30 years) and the moderating role of cultural norms on stigma. The implications of this study emphasize the importance of family-based interventions, such as stigma reduction programs and inclusive counseling, to strengthen social welfare policies that are sensitive to gender and sexual orientation in Indonesia.